Schaum's outline of theory and problems of programming with Pascal - Gottfried, Byron S (McGraw-Hill , New York, 1994)
Helps you: brush up before tests; find answers fast; study quickly and more effectively; and, get the big picture without spending hours poring over lengthy textbooks. This book includes: explanations of Pascal fundamentals; sample programs in Pascal; fully solved problems, with step-by-step solutions; and, hundreds of practice problems.
O level